BUSINESS DEVELOPMENT STRATEGY ANALYSIS (Case Study in Ucok Durian) - Fitri Berutu; Ricky Julius Salim; Rivael Rivaldo Situmorang; Januardin Manullang; Rintan Br. Saragih (Mount Hope Economic Global Journal, 2024)
The aim of this research is to analyze the strategies that influence Ucok Durian's business development. In this research, there are several strategies implemented by Ucok Durian in developing his business. Strategy is a program to determine and achieve company goals and implement its mission. In this study, researchers chose the location of UCok Durian, Medan City as a research location for conducting research on business development strategies. The method used in this research uses a qualitative research method with a descriptive approach, and the sources in this research consist of 3 sources, namely 1 (one) owner and 2 (two) consumers of ucok durian. Data collection for this research was carried out in interviews, observation and documentation. From the research results based on data collection, a strategy was obtained using SWOT analysis to determine the strengths, weaknesses, opportunities open to the company and a number of identified threats in maintaining product quality, improving service and product sales. The ucok durian business has weaknesses, especially in the use of technology and promotion, but also has the strength to improve these weaknesses. Based on the results of the interview, it was found that ucok durian also carried out a business development strategy through marketing communication strategies which were categorized as good through direct sales and through news in introducing durian products so that consumers were attracted and interested in making purchases.